(3GYOGO GdHQGeL GdEPGYjI h GdJdaRjhfjI (B/s - (3WGdH, YHO GdMSjfs; (3GdTejQjs ((3GdbGgQI (B:s (3OGQ GdcJGH GdMOjK ,s, 2014)
(3jJfGhd GdcJGH eLehYI ef GdGNJUGUGJ GdegfjI h GdafjI GdJj JSGge aj GeOGO QLd GdGYdGe HGdGLgRI GdafjI h GdgfOSjI h GdJcfhdhLjI GdJj jJYGed eYgG NdGd Yedg HGdhSGFd (B( (3GdebQhAI h GdeSehYI h GdeQFjI(B) (3aaj GdaUd GdGhd jJfGhd GdhSGFd GdegfjI dQLd GdGYdGe h ef VefgG eYQaI GdGYdGe GdGSdGej JGQjNjG eY GdJWQb Gdi eeGQSI YedjI GdJUhjQ GdahJhZQGaj dVeGf fLGM egeI GdeUhQ h GdeMQQ GdUMaj GeG GdaUd GdKGfj ajJWQb Gdi eYQaI JbfjGJ GdcGejQG GdahJhZQGajI h GSdhH GdMUhd Ydi GdUhQI GdegfjI GdJj JZfj ehVhY GdMOK HGdJaGUjd GdeWdhHI h GdGSJaGOI ef GdUhQ GdQbejI HhGSWI GdMGShH dGZfGA GdehVhY GdeWQhM GeG GdaUd GdKGdK ajDcO Ydi cjajI GYOGO fUhU GdHQGeL GdGPGYjI h GdJdjaRjhfjI h GfJbGA GdfUhU GdLjOI efgG h eYQaI fhYjI h JbfjI GdGSJOjhgGJ GdGPGYjI h GdJdjaRjhfjI h GdeOjQjGJ h GdGbSGe GdafjI GdJj JSGge aj fLGM YedjI GfJGL GdHQGeLs
(3HHdjhZQGajG (B: (3U(B.223-224s
Keywords: (3HQGeL GdEPGYIs; (3HQGeL GdJdjaRjhf s